Prasse, Karl-G. 2010. Tuareg Elementary Course - Souag, Lameen (Afrikanistik online, 2011)
The dialect discussed in this book, Tahaggart, is numerically insignificant in comparison, spoken in Algeria and Libya around the Ahaggar Mountains by hardly more than 50,000 people; however, it is of particular historical and anthropological interest for its relative isolation both from Arabic and from sub-Saharan African languages, and was the subject of some of the earliest comprehensive lexicography (Foucauld 1951). The author of the book under review, Karl-G. Prasse, has devoted much of his long career to the linguistic study of Tuareg, including his four-volume Manuel de grammaire touaregue (tahǎggart) (Prasse 1972). In this book he returns to the theme of Tuareg grammar, bringing to it the benefit of his intervening years' experience.
Keywords: Tahaggart; Touareg; Tuareg